PENGARUH KETERLIBATAN KERJA DAN ORGANIZATION CITIZENSHIP BEHAVIOUR(OCB)TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT UMUM (RSU) DEWI SARTIKA KOTA KENDARI YANG DIMEDIASI OLEH KEPUASAN KERJA - Rohayati Rohayati; Samdin Samdin; Muhammad Masri (Pascasarjana Universitas Halu Oleo, 2022)
The research objective is to find out; 1) the effect of job involvement on job satisfaction at Dewi Sartika Hospital, Kendari City. 2) the influence of organization citizenship behavior (OCB) on job satisfaction at Dewi Sartika General Hospital, Kendari City. 3) the effect of work involvement on employee performance at Dewi Sartika General Hospital, Kendari City. 4) the influence of organization citizenship behavior (OCB) on employee performance at Dewi Sartika General Hospital, Kendari City. 5) the effect of job satisfaction on employee performance at Dewi Sartika General Hospital, Kendari City. 6) the role of job satisfaction as mediating the effect of work involvement on employee performance at Dewi Sartika General Hospital, Kendari City. 7) the role of job satisfaction as mediating the influence of organization citizenship behavior (OCB) on employee performance at Dewi Sartika General Hospital, Kendari City. This research design uses a quantitative approach, with the type of explanatory research. The sampling technique in this study is non-probability sampling, ie the sampling method is not random. The data used are primary and secondary data. The data analysis method of this research is descriptive analysis and Partial Least Square (PLS). The results showed that; 1) Job involvement has a significant effect on job satisfaction. 2) Organization Citizenship Behavior (OCB) has a significant effect on job satisfaction. 3) work involvement has no significant effect on employee performance. 4) Organizational Citizenship Behavior (OCB) has a significant effect on employee performance. 5) job satisfaction has a significant effect on employee performance. 6) Job satisfaction is proven to play a role in mediating the effect of work involvement on employee performance. 7) Job satisfaction is proven to play a role in mediating the effect of organization citizenship behavior (OCB) on employee performance.